SKIN MICROCIRCULATORY ORGANIZATION TYPES IN ARTERIAL HYPERTENSION BY THE DATA OF DOPPLER FLOWMETRY - A. P. Vasiliev; N. N. Streltsova; M. A. Sekisova (Российский кардиологический журнал, 2015)
Aim. To assess types of functional shifts at the microcirculatory level (MC) in patients with arterial hypertension (AH) with different level of microvascular resistance. Material and methods. Healthy (n=34) volunteers and patients with AH 2-3 grade (n=79) and high (n=30) level of microvascular resistance of the skin were assessed for MC with laser doppler flowmetry.Results. No matter the comparable level of blood pressure (BP) in groups with AH, the differences of MC pattern in patients with high vascular resistance are the same and present with a venous congestion resulting in an intensification of arterial-venular shunting of the blood and decreased venous backflow. As the load of the blood coming into microcirculatory stream in the AH groups investigated is identical, constriction of precapillares and dumping of blood by shunts is related to significant decrease of nutritive blood flow. Negative character of microhaemocirculation in this case is confirmed by the higher prevalence of worse prognostic types of hemodynamics and higher microalbuminuria level.Conclusion. Decreased nutritive productivity of MC in patients with high microvascular resistance suggests more prominent negative influence on target organs that requires more active hypotensive therapy with consideration of MC shifts. Also the expediency cannot be disregarded of the inclusion of strong vasolytic agents in complex therapy.